2022
DOI: 10.1093/toxsci/kfac066
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Effects of an Environmentally Relevant Phthalate Mixture on Reproductive Parameters and Ovarian miRNA Expression in Female Rats

Abstract: Phthalates are endocrine-disrupting chemicals used in many consumer products. Our laboratory previously developed an environmentally relevant phthalate mixture consisting of six phthalates and found that it disrupted female fertility in mice. However, it was unknown if maternal exposure to the mixture affects reproductive parameters and ovarian post-transcription in the F1 and F2 generation of female rats. Thus, we tested the hypothesis that maternal exposure to the phthalate mixture affects folliculogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…According to our previous results, the rno‐miR184 and rno‐miR‐141‐3p expression profile on the ovary of directly exposed females (F1‐PND22) showed a different expression pattern compared to the ventral prostate of male offspring submitted to the same experimental protocol, at the same age, 15,18 showing that the epigenetic changes observed can be tissue, sex or phthalate mixture dependent 38,39 …”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…According to our previous results, the rno‐miR184 and rno‐miR‐141‐3p expression profile on the ovary of directly exposed females (F1‐PND22) showed a different expression pattern compared to the ventral prostate of male offspring submitted to the same experimental protocol, at the same age, 15,18 showing that the epigenetic changes observed can be tissue, sex or phthalate mixture dependent 38,39 …”
Section: Discussionmentioning
confidence: 66%
“…35,36 Our previous results showed that maternal exposure to a phthalate mixture altered the expression of microRNAs in the ovary and ventral prostate of rat offspring. 15,18 Likewise, phthalate monoester mixture exposure modulated benign and tumor human prostate cells and increased the expression of the miR-184 and miR-141-3p in vitro. 37 The results presented here agreed with the microRNA sequencing profile presented by Scarano et al 15 and were correlated with some oncogenic targets by in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations